Long-term imprisonment and human rights - Drenkhahn, Kirstin; Dudeck, Manuela; Dünkel, Frieder (Routledge frontiers of criminal justice, 2014)
"This book presents cutting-edge research on the living conditions of long-term prisoners in Europe and considers whether these conditions meet international human rights standards. Bringing together leading experts in the field, with comprehensive coverage of the issues in Belgium, Croatia, Denmark, England, Finland, France, Germany, Lithuania, Poland, Spain and Sweden, this book offers the first comparative study on the subject.Whereas past research in this area has concentrated on the Anglo-American experience, this book offers a truly comparative European approach and pays due attention to the differences in prison systems between the post-Soviet countries and continental Europe. "--